Obstacles and Challenges of Rural Development in Afghanistan: Examining Problems and Solutions: A Review a Comprehensive Study - Fayaz Gul Mazloum Yar; Janat Gul Zazia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
T This study comprehensively examines the multifaceted challenges impeding rural development in Afghanistan and proposes strategic recommendations for achieving sustainable growth. The research employs extensive document analysis, a critical review, and a literature review spanning 2020 to 2024, analyzing institutional, socio-cultural, economic, environmental, and infrastructural factors affecting rural development. The findings reveal that development is hindered by institutional obstacles such as ineffective governance, centralized planning, and a lack of coherent strategies, alongside socio-cultural issues like migration, low educational attainment, gender disparities, and economic barriers including poverty, unemployment, and limited market access. Environmental concerns such as land degradation and inadequate infrastructure further exacerbate these challenges. The study recommends a holistic approach, emphasizing decentralization, community engagement, infrastructure investment, sustainable agricultural practices, and vocational training to build local capacities. Collaborative efforts between stakeholders are essential to drive sustainable development in Afghanistan's rural areas.